2017
DOI: 10.2106/jbjs.16.00718
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Elevation as a Risk Factor for Slipped Capital Femoral Epiphysis Independent of Obesity Status

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 84 publications
(84 reference statements)
0
27
0
1
Order By: Relevance
“…The inconsistency between rising obesity rates in children, on the one hand, and stable rates for SCFE, on the other, together with the elevated risk of developing obesity in later life found in this study indicates that not only obesity per se but other factors associated with obesity may play a role in the etiology of SCFE. Halverson et al ( 2017 ) reported elevated serum leptin levels in patients with SCFE, regardless of their BMI, suggesting a shared risk factor for obesity and SCFE. Leptin is a cytokine-like hormone with proinflammatory properties known to be associated with autoimmune disorders, infections, and endocrine and metabolic diseases (Procaccini et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistency between rising obesity rates in children, on the one hand, and stable rates for SCFE, on the other, together with the elevated risk of developing obesity in later life found in this study indicates that not only obesity per se but other factors associated with obesity may play a role in the etiology of SCFE. Halverson et al ( 2017 ) reported elevated serum leptin levels in patients with SCFE, regardless of their BMI, suggesting a shared risk factor for obesity and SCFE. Leptin is a cytokine-like hormone with proinflammatory properties known to be associated with autoimmune disorders, infections, and endocrine and metabolic diseases (Procaccini et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, there have been other studies showing similar results [57, 58] and that the severity of SCFE increases as BMI increases [59], while the incidence of bilaterally SCFE also increases [60]. There are conflicting reports if SCFE is related to vitamin D intake [61], and yet, a new study shows an association between elevated serum leptin levels and SCFE, regardless of BMI [62]. This further demonstrates that SCFE is multifactorial disease that may not be strictly dependent on the altered biomechanics hypothesis.…”
Section: Main Textmentioning
confidence: 88%
“…Murray y Wilson confirmaron una estrecha correlación entre el aumento de la obesidad infantil en los últimos 20 años en Escocia y una incidencia creciente de DEFP (38) . Por otro lado, según Halvarson y colaboradores, la obesidad no es un factor suficiente para el desarrollo de DEFP, por lo que podría existir un factor independiente, como podría ser la hiperleptinemia, que sea capaz de explicar la alteración en el funcionamiento fisario (39) . Como limitaciones del presente estudio se destaca su naturaleza retrospectiva, el bajo número de pacientes y el corto seguimiento clínico radiológico para lograr evaluar las complicaciones a largo plazo (coxartrosis).…”
Section: Discussionunclassified